The First Auction of Non-Conventional Renewable Energy in Colombia: Results and Perspectives - Moreno, Ricardo; Larrahondo, Diego (International Journal of Energy Economics and Policy, 2020)
In Colombia, as a historic milestone, the first long-term auction of non-conventional renewable sources was held in 2019, with the aim of the National Government to take a major step in the energy transition policy. The auction organized by the Ministerio de Minas y EnergÃa (MME) defined the objectives, rules and type of auction. The results of the first auction indicate that eight project were selected by a pay-as-bid auction scheme, five wind and three solar projects will imitate operations at 2021accounting for 1298.8 MW. This paper presents a review of auction in various countries of South America in order to compare final prices for technology. Finally, this paper discusses perspectives for the energy sector in Colombia according to the implications of this auction. Keywords: Non-conventional Renewable Energy, Energy Policy, Auction Mechanism. JEL Classifications: O13, Q28, Q42, Q48 DOI: https://doi.org/10.32479/ijeep.10010